Treatment Of Palm Oil Mill Effluent (POME) Using Membrane Technology - Raja Ehsan Shah, Raja Shazrin Shah (2004)
Raw POME has a high biochemical oxygen demand (BOD) which is about one hundred times more than that of sewage. If not properly treated, POME could pose as a high organic pollutant. Conventional ponding process has been an effective method to reduce the biological and chemical constituents of POME. This method, even though simple and reliable, generates large amounts of sludge and takes up large land areas. It is thus justifiable that many studies have been conducted to develop alternative methods for POME treatment with possibilities of resource recovery by smaller, higher efficiency treatment system. In this report, we assessed the current technologies of POME treatment system and also some other biological wastewater treatment systems. We found that membrane technology has high potential of becoming part of POME treatment system. With a high separation capability, there is a possibility of developing systems that can recover valuable pharmaceutical components from POME and also recovering high quality water by application of membrane technology to POME treatment systems. Initial lab work and the current treatment applications have led us to select centrifugation as membrane pretreatment method. This is quite a good estimation of the three-phase-decanter system. The aqueous phase from his process have already removed from 60% to 80% of chemical oxygen demand (COD), turbidity, color, and suspended solids. This will be the feed to the hollow fiber membrane modules. The modules were of 0.2 Âµm, 500K, 100K, and 30K MWCOs. Our system as it is, have an overall removal efficiency of 89.9% for COD, 92.9% for colour, 99.4% for suspended solids and 97.9% for turbidity. These values are comparable to works done by other researchers [1] [2]. We could expect better removal and efficiencies if our pretreatment system is optimized.